PRA RANCANGAN PABRIK BRIKET ARANG DARI JERAMI PADI DENGAN KAPASITAS 1.900 TON/ TAHUN - Sugito, Bambang; Iskandar, Taufik; Abrina Anggraini, Sinar Perbawani (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Petroleum is a non-renewable energy, while oil is still a choice that will result in the depletion of oil reserves. One of the energy that needs to be addressed to develop is biomass as an alternative energy. Alternative technologies for utilizing biomass waste is a technology for making charcoal by pyrolysis. Charcoal briquettes can be used as an energy alternative to kerosene. The raw material charcoal briquettes can be made of various materials, such as rice straw. In this study, the material used is rice straw aims to determine the effect of particle size dankuat press the calorific value and the duration of the test flame from rice straw charcoal briquette. Rice straw is the material that is not so good to be used as charcoal briquettes, in accordance with the results of the highest calorific value is 3,100 cal and flame test longest time is 10501 seconds or 1: 52 min. While most high calorific content of only 2,913. So as to substitute alternative energy not so good according to SNI 1-6235-200. Keywords: Crude Oil, Biomass, Energy alternatives, rice straw, charcoal briquets.